PENGEMBANGAN MESIN PENCACAH JANGGEL JAGUNG UNTUK MENINGKATKAN KESEJAHTERAAN PETANI DESA CEPOKO - Jamilah Karaman; Muhammad Wildanul Ma’arif; Mohammad Irfan; Aziz Nurkholiq; Muhammad Hanif Rifai; Ermawati Almunawarah (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
The Thematic Community Service Program (KKN Tematik) is a concrete form of the university’s contribution to community engagement through the application of science and appropriate technology. One such activity is the development of a corn cob chopper machine in Cepoko Village, Ponorogo Regency, aimed at improving farmers’ welfare by utilizing agricultural waste that has not been optimally used. This project applies the Participatory Action Research (PAR) method, involving the community actively from the stages of problem identification, design, machine fabrication, to the use of chopped materials for fermented animal feed. The results show that the machine improves waste processing efficiency, produces versatile products, and creates new business opportunities. Environmentally, it reduces waste burning, while economically, it lowers livestock feed costs. Thematic KKN serves not only as a learning platform for students but also promotes innovation and economic empowerment within rural communities.